Comparative evaluation of voltage conversion and encoder pulse detection methods for controlling a model high-bay warehouse - Anas Abu Al-Hija’a; B. J. Szekeres; M. Andó (Discover Applied Sciences)
Abstract This study evaluates five control methods for the Fischertechnik Training Factory Industry 4.0–24 V system, focusing on accuracy, efficiency, and performance in managing voltage differences and encoder pulse detection. The proposed method introduces a novel approach by integrating a dedicated pulse-counting Arduino with the TBD62783APG chip, enhancing precision and reliability beyond traditional methods. Despite requiring additional hardware, this method demonstrated exceptional control and dependable operation, showcasing the efficacy of specialized integrated circuits in industrial automation applications. The presented evaluation enhances control strategies for industrial automation, emphasizing efficient voltage conversion and precise encoder pulse detection to enhance system performance and reliability, laying the groundwork for future advancements in remote control capabilities and complex manufacturing systems.